Physiological aspects of educational training adaptation of students - H. G. Galstyan; S. M. Minasyan (Acta Biomedica Scientifica, 2015)
20 healthy male and female students of Artsakh State University aged 18-20 years have participated in an experiment to study the mechanisms of training adaptation. Surveys were conducted during the academic semester in 2 stages: the non-examination period (March-April) - Monday and Friday, before and after school and during the examination period (May-June) - before and after the exam. In order to study the impact of mental stress a survey was also conducted among students once they complete mental or intellectual Eysenck test. A psychological testing of students was carried out to identify the level of intelligence (IQ) by Eysenck, personal and situational anxiety by Spielberger and health, activity, mood by SAN (HAM) questionnaire. Basic hemodynamic parameters were measured: heart rate, systolic and diastolic blood pressure. ECG examination was conducted using R.M. Baevsky's cardio-ervalography method. Comparative analysis of the dynamics of the studied parameters showed that the process of adaptation of students to the teaching load is accompanied by periods of decline during non-examination period, more vividly expressed when doing mental or intellectual work, and tension of the studied parameters during the examination period.